Caracterização do perfil comportamental do roedor neotropical proechimys - Marques, Marcia Jonathas Guimarães [UNIFESP] (2016)
Introduction: Proechimys belong to the family Echimidae and are distributed by Neotropiais forests of South America These rodents develop important role in environmental reforestation and in recent years aroused great interest in the area of health. Goal: Describe the biological and behavioral characteristics of the Neotropical rodent Prochimys in biotery. Methods: Physical and biological characteristics of adult males Proechimys rodents, raised in biotery, were observed. They also underwent a series of behavioral tests in order to describe their behavior and cognitive characteristics, such as memory, learning, anxiety, locomotor activity and habituation to a new environment. The following tests were used: Morris water maze, T maze, spatial working memory test, plus-maze discriminative avoidance task, elevated plus-maze and open field. Locomotor activity was investigated through the catwalk device. Adult Wistar rats were subjected to the same experimental behavioral protocols in order to validate the tests. Results and Conclusions: Proechimys and Wistar rodents showed similar working memory profile in the maze T test and in the operacional memory task. In plus-maze discriminative avoidance task, Proechimys showed stronger anxiety-like behaviour than Wistar rats, during the first presentation to the apparatus. But when they were resubmitted to the device, the anxiety-like behaviour of Proechimys equals the Wistar. The locomotor activity in the aversive context is greater in Proechimys, in both training period and in the first test, which was three hours performed after training. But, 24 hours later and seven days of training, both animal species explored the apparatus in similar manner. During training, both groups learned successfully the proposed task. In the memory test, three hours after training, the two species of animals recalled the aversive arm. But, after 24 hours, only the Wistar rats remembered the aversive stimulus. However, after seven days of training, either species didn´t recalled the aversive stimulus. The lag time analysis, three hours after training, Proechimys rodents exhibited better memory of the aversive arm than Wistar rats, but there was no difference between the two species in the other times studied. Difference in emotionality between these two species was evident in the elevated plus maze since. Proechimys showed greater anxiety-like behavior than the Wistar. In the elevated plus maze, Proechimys showed greater anxiety-like behavior than the Wistar, however, no changes in locomotor activity were observed in both species. In the open field test, Proechimys presented similar locomotor activity as Wistar rat, and both species spent substantially more time in the peripheral area of the apparatus. Curiously, Proechimys spent much more time in the center of the open field, a behavior usually correlated with decreased anxiety. But, in a contradictory way, Proechimys produced higher amounts of fecal boli than Wistar. All animals were evaluated for gait and showed locomotor activity preserved.